2014
DOI: 10.1002/prp2.82
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CYP3a expression and activity in mice models of type 1 and type 2 diabetes

Abstract: CYP3A4, the most abundant cytochrome P450 enzyme in the human liver and small intestine, is responsible for the metabolism of about 50% of all marketed drugs. Numerous pathophysiological factors, such as diabetes and obesity, were shown to affect CYP3A activity. Evidences suggest that drug disposition is altered in type 1 (T1D) and type 2 diabetes (T2D). The objective was to evaluate the effect of T1D and T2D on hepatic and intestinal CYP3a drug-metabolizing activity/expression in mice. Hepatic and intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Though midazolam and testosterone are both substrates of human CYP3A4 (mouse CYP3a11), CYP3A4 is characterized by a large substrate‐binding pocket containing six substrate recognition sites . Previous studies showed that the change of activities of midazolam‐1‐hydroxylation and testosterone‐6β‐hydroxylation mediated by CYP3A4 or CYP3a11 were different and diabetes had different effects on these substrate recognition sites . Similar results were observed in the present study, indicating that the effect of diabetes mellitus on Cyp3a11 activity might vary with the substrate.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Though midazolam and testosterone are both substrates of human CYP3A4 (mouse CYP3a11), CYP3A4 is characterized by a large substrate‐binding pocket containing six substrate recognition sites . Previous studies showed that the change of activities of midazolam‐1‐hydroxylation and testosterone‐6β‐hydroxylation mediated by CYP3A4 or CYP3a11 were different and diabetes had different effects on these substrate recognition sites . Similar results were observed in the present study, indicating that the effect of diabetes mellitus on Cyp3a11 activity might vary with the substrate.…”
Section: Discussionsupporting
confidence: 87%
“…Although it is known that Cyp2b10 and Cyp4a mRNA and protein levels increase, Cyp1a2 protein levels decrease, and the activities of Cpy3a11 , Cyp2b10 and Cyp2c29 increase in db/db mice, to date, changes in other CYP enzymes activities and UGT enzyme activities have not been reported in db/db mice. In this study, the activities of the main drug‐metabolizing enzymes, including eight CYP‐mediated, nine phase I metabolic reactions and three UGT‐mediated glucuronidation reactions were fully studied in db/db mice.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations